ANALYSIS ON SINGIFICANT IMPACT OF PSYCHOLOGICAL EDUCATION AND TEACHING MODE - Dr., Priti Srivastava (International Journal of Psychosocial Rehabilitation, 2015)
The mode of psychological education and teaching has a considerable impact on the ultimate effect of education and teaching, therefore actively supporting the reform of education and teaching has a conspicuous practical value in the teaching environment and teaching objectives. With the widespread use of computer technology in education and the popularisation of network applications, the methods and modes of education and teaching are beginning to grow in a diverse fashion, according to the analysis of educational and teaching practise at this stage. For the sixth semester, the Cumulative Grade Point Average (CGPA) was predicted using data from the matriculate and preuniversity examinations, as well as grades from the previous four semesters and other learning and study skills. Both Neural Network and Decision Tree were employed to investigate the impact of students’ psychology on prediction, with the latter being used to classify failures in the sixth semester. Coefficients of correlation R and Mean Squared Error were used to gauge the models’ overall performance. The accuracy of the forecast improves by 4 to 6 percentage points. According to the findings, a student’s motivation level, perception of knowledge, and usage of available study tools all factor towards how well they will perform on the exam.